"Palatable Foreign Control": British money doctors and central banking in South America, 1924-1935 - Marcelo de Paiva Abreu; Pedro Carvalho Loureiro de Souza (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2011)
This article is on the activities of British money doctors in South America between the 1890s and the 1930s, hitherto overlooked in the literature. It focuses on Sir Otto Niemeyer's missions to Brazil and Argentina in the early 1930s compared to his earlier report on New Zealand and Professor Edwin Kemmerer's report on Chile in the mid-1920s. The impact of their visits on the market evaluation of risk related to bonds ?oated by the largest South American economies is quantitatively analyzed. Dificulties involved in generalizations about links between policy proposals and market evaluation enhance the interest of studying speci?c experiences. Niemeyer's general proposals to the Brazilian government in mid-1931 advising on a possible return to the gold standard are evaluated. His speci?c proposals on central banking in New Zealand, Argentina and Brazil are discussed in contrast with Kemmerer's proposals in Chile. The focus is on the autonomy of central banks, representation of sectoral interests, the role of gold in total foreign exchange reserves, and the exertion of foreign in?uence though directors, shareholders and permanent experts. Finally, the realism of proposals is evaluated in the context of contemporary economic conditions compared with advice provided by other experts on related issues
Keywords: 330; Geldpolitik; Politikberatung; Briten; Südamerika